Cancer Prevention Begins in Middle School: The Personal Advantages of HPV Immunization in Males. (May 2023) - Gordon, Jenny; Bail, Jennifer
The human papillomavirus (HPV) is the most common sexually transmitted infection in the United States despite most cases being preventable by vaccination. HPV vaccine efficacy varies in relationship to when the vaccine is administered, with greater efficacy obtained if administered prior to sexual debut. Historically, this vaccine was created to protect women from cervical cancer. As scientific knowledge of HPV-related cancers has advanced, it has become evident that HPV vaccination is a priority for both genders. HPV is known to contribute to male cancers of the mouth, throat, anus, and penis, as well as causing genital warts. This article aims to explain the benefits of HPV immunization for the gender the farthest from meeting vaccination goals, boys, and young men. This article expounds on the school nurses' role in promoting vaccination to prevent HPV infection and the sequela of related cancers.